Postpartum-Isolated Native Pulmonic Valve Methicillin-Resistant Staphylococcus aureus Infective Endocarditis Complicated by Pelvic Abscess, Clavicle Osteomyelitis, and Polyarticular Septic Arthritis - Daniela Navarrete; David Hannibal; Sachin M. Patil; Tarang Pankaj Patel; William Roland (Case Reports in Infectious Diseases)
Isolated native pulmonic valve infective endocarditis (IE) is a rare occurrence. The most commonly involved valves in injection drug users are the tricuspid valve followed by mitral and then aortic valves. Most reported cases of methicillin-resistant Staphylococcus aureus (MRSA) IE involve multiple valves. Isolated involvement of the pulmonic valve in IE is infrequent, especially in intravenous drug users or patients with indwelling catheters, prosthetic valves, or implantable cardiac devices. Here, we report a young postpartum female patient with isolated native pulmonic valve MRSA IE with MRSA bacteremia and history of active injection drug use. A PubMed literature review revealed a single described prior case report in a postpartum female. The patient’s clinical course was complicated by a large native pulmonic valve vegetation, septic pulmonary emboli, pelvic abscess, polyarticular septic arthritis, and clavicular osteomyelitis. The patient underwent bioprosthetic pulmonic valve replacement and finished six weeks of intravenous vancomycin for complete recovery.